2022
DOI: 10.21203/rs.3.rs-1825106/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Downregulation of miR-211 expression in blood plasma of infertile men compared to the fertile controls

Abstract: Background: Infertility is defined as the inability of a couple to conceive after one year of having regular unprotected sex. Changes in the expressions of miRNAs are associated with impaired spermatogenesis and can be used as potential biomarkers of infertility in males. This study aimed to evaluate the expression levels of miR-211 as a predictive factor in plasma samples of intertile men compared to the controls Methods: In this case-control study, blood plasma samples were taken from the infertile men (n=10… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…2 In this study, Naeimi et al focus on the potential role of circulating miR-211 levels in diagnosing male infertility, specifically in patients with nonobstructive azoospermia or severe oligozoospermia. 1 It demonstrates that infertile men exhibit significantly lower plasma miR-211 levels compared with a control group, establishing a strong correlation with various sperm parameters. These results suggest that miR-211 could serve as a valuable biomarker for evaluating spermatogenesisrelated infertility, offering a new approach to the diagnosis and assessment of male reproductive health issues.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…2 In this study, Naeimi et al focus on the potential role of circulating miR-211 levels in diagnosing male infertility, specifically in patients with nonobstructive azoospermia or severe oligozoospermia. 1 It demonstrates that infertile men exhibit significantly lower plasma miR-211 levels compared with a control group, establishing a strong correlation with various sperm parameters. These results suggest that miR-211 could serve as a valuable biomarker for evaluating spermatogenesisrelated infertility, offering a new approach to the diagnosis and assessment of male reproductive health issues.…”
mentioning
confidence: 91%
“…Dear Editor, I read with great interest the study by Naeimi et al, published in the International Journal of Urology. 1 Recent years have seen a growing recognition of the clinical significance of non-coding RNAs. Among these, the diagnostic capability of circulating miRNAs for various diseases has been extensively reported in the literature.…”
mentioning
confidence: 99%
“…Circulating miRNAs are good potential candidates for male infertility, and due to their size, abundance, detection at low concentrations, tissue specificity, and relative stability, they can have the potential capacity of a new noninvasive biomarker. 2 Our previous study showed that the distribution of CHD5 genotypes and frequency of alleles were statistically significant between infertile men and control groups and proposed that CHD5 polymorphism (rs9434741) could be associated with the risk of male infertility. 3 We discussed that the CHD5 gene plays a role in sperm density and there was shown a close connection between miR-211 and the CHD5 gene expression.…”
mentioning
confidence: 96%